Application of Arbuscular Mycorrhizal Fungus (AMF) improves the growth of single-bud sugarcane (Saccharum officinarum L.) seedlings from different bud location. Issue 1 (April 2020) - Musa, Y; Ridwan, I; Ponto, H; Ala, A; M Farid, BDR; Widiayani, N; Yayank, A R
Abstract: This study aimed to study the effect of different doses of arbuscular mycorrhizal fungi (AMF) on the growth of sugarcane seedlings ( Saccharum officinarum L.) planted through a single-bud method with different buds location. The study was conducted at the Faculty of Agriculture's Experimental Garden, Universitas Hasanuddin, Makassar, South Sulawesi. The study was carried out from July to November 2018 and set using a Randomized Block Design. Four doses of AMF were used i.e. 2, 4, 6, and 8 g/polybag, respectively and three sugar cane seedling buds location namely apical, median and basal end were used. The results show that the use of single buds from the upper buds showed better growth of shoots at the beginning of growth up to 4 weeks after planting (WAP), which was shown by shoot height parameters. In addition, the location of the upper bud also produced highest number of leaves and number of bud segments. The application of AMF with a dose of 8 g/polybag on the single-bud seedling of upper shoot showed the biggest stem diameter parameter values.